Exemplar partner or controversial outsider? Huawei’s strategic engagement in Oceania - Lin, Jake (Henry Stewart Talks, 2021)
The unprecedented case of Huawei, Business caught in geopolitics, The nature of conflict and the Huawei model, Marketing strategies, Precarious relations with the state, Problematic labour relations